Antimony doping to enhance luminescence of tin(iv)-based hybrid metal halides. Issue 15 (23rd June 2022) - Liu, Kunjie; Hao, Shiqiang; Cao, Jindong; Lin, Jiawei; Fan, Liubing; Zhang, Xusheng; Guo, Zhongnan; Wolverton, Christopher; Zhao, Jing; Liu, Quanlin
Abstract : Exploration of Sn 4+ -based organic–inorganic metal halides and suggests an efficient lone-pair-containing cation doping route to enhance the luminescent performance. Abstract : Lead-based organic–inorganic metal halides (OIMHs) have recently attracted special attention due to their efficient broadband photoluminescence. However, the toxicity of lead poses a challenge for their further development. Here, we selected Sn(iv ) as the metal center to synthesize the environmentally friendly and stable luminescent OIMHs (C9 H15 N3 )2 SnCl8 and (C9 H15 N3 )2 SnBr8 (C9 H13 N3 is 1-(2-pyridyl)piperazine). Both compounds possess zero-dimensional structures, crystallizing in the monoclinic space group P 21 / c, and their optical band gaps were experimentally determined to be 3.19 and 2.60 eV, respectively. Under UV excitation at room temperature, (C9 H15 N3 )2 SnCl8 exhibited double-peak emissions centered at 405 and 688 nm, which were attributed to the organic cation and inorganic octahedra, respectively. Upon introducing 5s 2 -lone-pair-containing Sb 3+ in (C9 H15 N3 )2 SnCl8, self-trapped emission was promoted, and the photoluminescence quantum yield increased from ∼1% to ∼17.84%. This work suggests effective strategies for finding environmentally friendly stable OIMHs and for further enhancing the luminescence properties through lone-pair-containing cation doping.